2015
DOI: 10.1002/anie.201505307
|View full text |Cite
|
Sign up to set email alerts
|

Function‐Led Design of Aerogels: Self‐Assembly of Alloyed PdNi Hollow Nanospheres for Efficient Electrocatalysis

Abstract: One plausible approach to endow aerogels with specific properties while preserving their other attributes is to fine-tune the building blocks. However, the preparation of metallic aerogels with designated properties, for example catalytically beneficial morphologies and transition-metal doping, still remains a challenge. Here, we report on the first aerogel electrocatalyst composed entirely of alloyed PdNi hollow nanospheres (HNSs) with controllable chemical composition and shell thickness. The combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
176
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(186 citation statements)
references
References 35 publications
3
176
0
5
Order By: Relevance
“…The mass peak current density of the Pd/ATN-BP catalyst is very high with a value of 5023.8 mA mg Pd ), respectively. Compared with, the mass peak current density of the Pd/ATN-BP catalysts in this study was higher than those of previously reported Pd-and Pt-based EOR catalysts, including the open-mouthed, yolkshell (OM-YS) Au@AgPd, [38] Pd 40 Ni 43 P 17 , [4] Pd 83 Ni 17 hollow nanospheres (HNS) aerogel, [39] Pd-Pt-Ag nanosheets, [40] Pd@ CoP nanosheets (NSs)/carbon fiber cloth (CFC), [41] Pd 7 /Ru 1 , [42] Pd 68 /Cu 32 , [43] PdCo nanotube arrays (NTAs)/CFC, [44] Fe-PdFe 2 O 3 (3:5)/MWNTs, [45] Pd/B, N-codoped graphene nanoribbons (BN-GNRs), [46] Au@Pd core-shell nanorods [47] and ternary NiAuPt nanoparticles on reduced graphene oxide (rGO) nanosheets (Ni 40 Au 33 Pt 27 -NGs) [48] catalysts shown in Figure 8a. Because of the high synergistic interaction between the Pd NPs and ATN-BP and the structural contribution, the obtained Pd/ATN-BP catalyst shows relatively high mass activity for the EOR.…”
Section: Resultsmentioning
confidence: 54%
“…The mass peak current density of the Pd/ATN-BP catalyst is very high with a value of 5023.8 mA mg Pd ), respectively. Compared with, the mass peak current density of the Pd/ATN-BP catalysts in this study was higher than those of previously reported Pd-and Pt-based EOR catalysts, including the open-mouthed, yolkshell (OM-YS) Au@AgPd, [38] Pd 40 Ni 43 P 17 , [4] Pd 83 Ni 17 hollow nanospheres (HNS) aerogel, [39] Pd-Pt-Ag nanosheets, [40] Pd@ CoP nanosheets (NSs)/carbon fiber cloth (CFC), [41] Pd 7 /Ru 1 , [42] Pd 68 /Cu 32 , [43] PdCo nanotube arrays (NTAs)/CFC, [44] Fe-PdFe 2 O 3 (3:5)/MWNTs, [45] Pd/B, N-codoped graphene nanoribbons (BN-GNRs), [46] Au@Pd core-shell nanorods [47] and ternary NiAuPt nanoparticles on reduced graphene oxide (rGO) nanosheets (Ni 40 Au 33 Pt 27 -NGs) [48] catalysts shown in Figure 8a. Because of the high synergistic interaction between the Pd NPs and ATN-BP and the structural contribution, the obtained Pd/ATN-BP catalyst shows relatively high mass activity for the EOR.…”
Section: Resultsmentioning
confidence: 54%
“…Examined parameters of EOR such as onset potential reaction and long-term stability show that among a series of graphene (G)-supported Ni x Pd 100−x binary alloyed catalysts, Ni 50 Pd 50 /G catalyst exhibits 60 mV lower onset potential compare to Ni 0 Pd 100 /G catalysts and current density approximately 8, 4, and 1.7 times superior than that of Ni 75 Pd 25 , Ni 0 Pd 100 /G, and Ni 25 Pd 75 /G catalysts, respectively [6]. The mass activity of the Pd 83 Ni 17 hollow nanospheres aerogel is 5.6-fold higher than that of the commercial Pd/C catalyst [14] while the mass activity of porous bimetallic PdNi catalyst is 3.5 times higher compared to the commercial Pd/C [15]. It is revealed that the onset potential is 80 mV lower and the peak current is about 3 times higher for ethanol oxidation using multi-walled carbon nanotubes (MWCNT) catalysts with Pd 1 Ni 1.5 compared to those of Pd/MWCNTs due to the small particle size and high crystallinity of binary catalyst [16] although it can be found that binary Pd 3.7 Ni 1 nanocatalyst with ultra-low loading of metals immobilized on MWCNT exhibits anodic current density over 11 times higher than on the Pd/MWCNT [17].…”
Section: Introductionmentioning
confidence: 91%
“…Recently, PdNi hollow nanospheres (HNSs) were employed as NBBs to fabricate a hierarchical aerogel with a well-defined 3D necklace-like network structure (Figure 4a-c). [41] The hollow cavity distributed throughout the networks could further be identified by a distinct peak (at ca. 22 nm) in the pore size distribution analysis (Figure 3f).…”
Section: Hierarchical Aerogelsmentioning
confidence: 98%
“…[25,26,[38][39][40] Linking aerogel research and nanotechnology, hierarchical aerogels with primary and secondary pore structures, built from shapeengineered NPs, have also been reported in the form of either hollow shell or dendritic particles. [41][42][43] As illustrated in Figure 1, the general synthesis of noble metal aerogels via the sol-gel process consists of three steps: i) the synthesis of nano-sized building blocks (NBBs); ii) the gelation of the NBBs into hydrogels (plus shape-control of the hydrogel) and iii) the supercritical drying of the hydrogel to yield an aerogel. These three strategies are outlined in different colors in paths I (B1-H1-A1), II (B1-H1-H2-A2) and III (B1-B2-H3-A3) of Figure 1.…”
Section: Synthesis and Featuresmentioning
confidence: 99%
See 1 more Smart Citation